(untitled) (Tempo e Argumento, 2017)
This article examines the character Bob Cuspe, created by the cartoonist Angeli, in the light of the concept of ‘counterbehavior,’ i.e. as innovative forms of political resistance that are grounded in the demobilization of power networks and their representatives. By examining the character – specifically the characteristics set out in the inaugural story –, and the discursive references applied to provide it with meaning, we aim to point out how its lifestyle expresses new contemporary resistance forms, insofar as it constitutes a new world, with rules of its own to interact and be together and, at the same time, it keeps a critical condition in mind. This analysis intends to refute the argument, usual in studies about this, that the character manifests a condition alienated from the social and political context in which it is inserted. Finally, we advocate the premise that the magazine Chiclete com Banana, where the Bob Cuspe’s stories were published, was a space created to reverberate an assumedly melancholic and nihilistic mood, which is not identified with the revolutionary intents and/or utopias of the previous generation of artists, politicians, and intellectuals, and this becomes representative of a large part of the Brazilian youth that grew up silenced and under the impact of fear promoted by the dictatorial State terror. Keywords: Comic Strips. Angeli, 1956. Graphic Humor.